2019
DOI: 10.17015/ejbe.2019.023.01
|View full text |Cite
|
Sign up to set email alerts
|

Negative Marketing in Political Campaigns and Its Effect on the Voting Decision of the Indian Millennial

Abstract: In an unprecedented event, the current ruling party of India -the BJP -won the UP election in 2017 after 15 years of domination by the Congress. In 2016, when all the pollsters and pundits statistically analyzed the ongoing election for US Presidency and predicted a Hillary Clinton victory, they all got it wrong. While the results seem miraculous in the eyes of the experts, the careful strategy executed by the political campaigners of all these parties involved a unique process of market segmentation, but more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Research by Svetlik [14] show that voters perceive this form of advertising as one that offers them more information, attract a greater degree of attention and more trust than in the case of positive advertising. Meanwhile, Hamelin et al [15] found that a mere 60 seconds was enough to heighten the participant emotional state and significantly alter participant perception and ratings about these politicians.…”
Section: Introductionmentioning
confidence: 99%
“…Research by Svetlik [14] show that voters perceive this form of advertising as one that offers them more information, attract a greater degree of attention and more trust than in the case of positive advertising. Meanwhile, Hamelin et al [15] found that a mere 60 seconds was enough to heighten the participant emotional state and significantly alter participant perception and ratings about these politicians.…”
Section: Introductionmentioning
confidence: 99%